Performance of optical OFDM systems using new PAPR reduction approach - Hilal Adnan, Fadhil; Hasoon, Feras N.; Syed Alwee Aljunid, Syed Junid; Ahmad, H. Y.; Hamza Mohammed Ridha, Al-Khafaji (EBSCO Publishing., 2013)
Link to publisher's homepage at http://connection.ebscohost.com/